1993
DOI: 10.1021/j100116a016
|View full text |Cite
|
Sign up to set email alerts
|

The ethylperoxy radical: its ultraviolet spectrum, self-reaction, and reaction with hydroperoxy, each studied as a function of temperature

Abstract: The ultraviolet spectrum of the ethylperoxy radical (C2H502) and the reactions C2H5O2 + C2H5O2 -products (1) and C2H5O2 + H02 -C2H502H + 0 2 ( 5 ) have been studied using the flash photolysis/UV absorption technique. The spectrum was taken between the wavelengths of 210 and 290 nm and at the temperatures of 298 and 600 K. The room temperature spectrum is found to be in good agreement with previous determinations, with a maximum cross section umax = (4.89 f 0.60) X lo-'* cm2 molecule-' at 240 nm. The temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
83
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(95 citation statements)
references
References 15 publications
12
83
0
Order By: Relevance
“…As shown in Fig. 4C, the ethyl peroxy radical spectrum measured herein is in excellent agreement with those of Wallington et al 25, Maricq and Wallington 24, Bauer et al 26, Fenter et al 27, and the recommendation of Tyndall et al 4, but is significantly different from that reported by Munk et al 28. The present study was performed in the same laboratory using essentially the same apparatus as employed by Munk et al 28 and the difference in results deserves comment.…”
Section: Discussionsupporting
confidence: 90%
“…As shown in Fig. 4C, the ethyl peroxy radical spectrum measured herein is in excellent agreement with those of Wallington et al 25, Maricq and Wallington 24, Bauer et al 26, Fenter et al 27, and the recommendation of Tyndall et al 4, but is significantly different from that reported by Munk et al 28. The present study was performed in the same laboratory using essentially the same apparatus as employed by Munk et al 28 and the difference in results deserves comment.…”
Section: Discussionsupporting
confidence: 90%
“…At 500–600 K, peroxy radical isomerization reactions compete with bimolecular reactions (e.g., cross-combination and recombination of RO 2 ) and formation of dimer compounds ( 1 , 18 ). For example, the rate constant of RO 2 + RO 2 (e.g., C 2 H 5 O 2 + C 2 H 5 O 2 ) is on the order of 10 10 cm 3 ⋅mol −1 ⋅s −1 at 298 K and has a weak negative temperature dependence ( 31 ), while the intramolecular H-atom abstraction of the RO 2 radical via a six-membered-ring transition state is on the order of 10 −3 s −1 at 298 K ( 23 ). However, the intramolecular H-atom abstraction is strongly temperature dependent and its rate is on the order of 10 4 s −1 at 550 K ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…12,14,15 The concentration of the methyl formate radical present at the measured delay time following laser photolysis is dependent on the initial reactions ͑2͒ and ͑3͒ as well as the following secondary reactions: The initial atomic chlorine, or fluorine, concentration is determined by calibration against ethylperoxy radical; Ϸ2-3 Torr ethane and Ϸ25 Torr O 2 are substituted for methyl formate plus a portion of the N 2 buffer, while maintaining the same amount of Cl 2 or F 2 as in the corresponding methyl formate radical measurement, and the C 2 H 5 O 2 concentration is measured via its previously reported UV cross section.…”
Section: A Experimental Methodsmentioning
confidence: 99%